Broadband industry structure and cybercrime: An empirical analysis - Carolyn Gideon; Christiaan Hogendorn (International Telecommunications Society (ITS), 2015)
Prior studies have shown that while ISPs are well positioned to provide residential and SME users critical protection from cybercrime, their incentives to do so are often insufficient. The presence of competition in providing broadband service is a factor we might expect to impact such incentives as shown in prior theoretical work. We test this finding using data consisting of intrusion attempts on residential networks obtained using honeypot sensors. We compare the frequency and nature of attack attempts found on networks served by ISPs that are monopolists with those that face competition. We also place sensors on servers to identify the IP addresses of the infected machines that conduct these attacks in order to analyze the infection rates of residential ISP networks.
Keywords: 330